Citotoxicidade transdentinária e efeito da carbodiimida (EDC) na biomodificação do colágeno dentinário e na degradação da interface adesiva - Scheffel, Debora Lopes Salles [UNESP] (2013)
The purpose of this study was to evaluate the trandentinal cytotoxicity of carbodiimide (EDC), as well as its influence on dentinal collagen degradation and stability of resin-dentin bonds. In the first experiment, MDPC-23 cells were seeded on the pulp surface of the disks and one of the following solutions was applied on the occlusal surface for 60s: no treatment (negative control), 0.1M, 0.3M or 0.5M EDC; 5% glutaraldehyde (GA); Sorensen buffer or 29% hydrogen peroxide (positive control). Cell viability and morphology were analyzed by MTT, Live/Dead assays, total protein (TP) and collagen production and SEM. Data were analyzed by Kruskal-Wallis and Mann-Whitney tests (p<0.05). Only GA increased cellular metabolism. Cell death by necrosis and cell morphology were not affected by the cross-linker agents. There was no reduction in TP and collagen production after 7 days. For the second experiment, dentin beams were completely demineralized and the variation in elastic modulus (E), MMP activity, dry mass loss, hydroxyproline release (HYP) and collagen thermal degradation (CTD) were analyzed after the dentin treatment for 30s or 60s with the following solutions: water; 0.5M; 1M or 2M EDC and 10% GA. Data from E and MMP activity and HYP release were submitted to Wilcoxon and Kruskal-Wallis or Mann-Whitney tests. Dry mass loss and CTD data were analyzed by ANOVA and Tukey’s tests (p>0.05). GA group obtained the highest E values. All cross-linking agents decreased MMP activity and HYP release and increased CTD. In the third experiment, sixty dentin beams were randomly divided into 6 groups according to the treatment solution: deionized water (control), 0.1M EDC, 0.5M EDC, 0.5M EDC+35% HEMA, 5% proanthocyanidin (PA) or 2% chlorhexidine (CHX). The beams were acid etched and treated for 60s. The total MMP activity was analyzed by a colorimetric assay (Sensolyte®). Data were expressed as absorbance values...